Cross-cultural counseling clinical case examples - Darby, George E.; Ivey, Allen E.; Shizuru, Lannette S.; Microtraining Associates ([Framington, Mass.] : Distributed by Microtraining Associates, 1981)
Shows a Cross cultural couseling sessions with three clinical case. First interview is about caucasian Dyad, second is Japanese-American Dyad and the last one is on cultural conflict
Title from title screen
Consultant: Paul Pederson
Keywords: Cross-cultural counseling; Counseling -- Cross-cultural studies; Psychotherapy -- Cross-cultural studies